1983
DOI: 10.1530/jrf.0.0680407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various proteinase inhibitors on ovulation of explanted hamster ovaries

Abstract: Hamster ovaries explanted at 21:00-24:00 h on the day of pro-oestrus were incubated with microbial proteinase inhibitors until 10:30 h on the next morning and the ovulatory blocking effect of these inhibitors was examined. Amongst 11 proteinase inhibitors examined, talopeptin, a specific inhibitor for metallo-proteinases, and alpha-MAPI, a specific inhibitor for serine and thiol proteinases, were the strongest blockers. These 2 inhibitors exhibited a chronological discrepancy in their blocking effect on ovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Many studies have demonstrated that MMPs play important roles in folliculogenesis, including development, luteinization, and luteolysis. Injection of synthetic metalloproteinase inhibitors has blocked ovulation in hamsters and rats [18,19]. Others have shown that MMP-1 protein and its enzymatic activity of ovine and rabbit ovaries were concentrated at the site of future rupture in the capillary lumina at the apex of the follicle [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that MMPs play important roles in folliculogenesis, including development, luteinization, and luteolysis. Injection of synthetic metalloproteinase inhibitors has blocked ovulation in hamsters and rats [18,19]. Others have shown that MMP-1 protein and its enzymatic activity of ovine and rabbit ovaries were concentrated at the site of future rupture in the capillary lumina at the apex of the follicle [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…7 describes the effect of benzamidine; similar dose response.was obtained with €-amino caproic acid). Similarly, several inhibitors of serine proteases inhibited in vitro ovulation of hamster ovaries (Ichikawa et al, 1983). Even though follicular rupture occurs 9-12 h after hCG stimulation, administration of inhibitors of serine proteases prior to 1.5 h after hCG blocked ovulation in rats (> 65%) but had limited effect « 30%) after 3 h. This result implies that the activity of serine proteases is required only during the first 3 h after hCG stimulation.…”
Section: -------------------------------------- Cmentioning
confidence: 88%
“…In mammals, ICHIKAWA et al 21) suggested that serine-proteinase(s) participate in ovulation, since specific inhibitors to these enzymes inhibit ovulation. BEERS22) and BEERS et al 23) reported that plasmin, one of the serine-proteinases, is capable of inducing ovulation since the plasminogen activator activity in the ovarian follicle usually increases with the approach of ovulation or in response to LH or cyclic AMP.…”
Section: Discussionmentioning
confidence: 99%